1998
DOI: 10.1002/(sici)1097-4628(19981024)70:4<717::aid-app11>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative polymerization of phenylenediamines by enzyme and magnetic properties of the products

Abstract: Oxidative polymerization of m-phenylenediamine was carried out using H 2 O 2 as an oxidant and horseradish peroxidase as a catalyst in mixtures of aqueous buffer solution and 1,4-dioxane or in reversed micellar solutions. When the reaction mixture was brought into contact with a stainless steel stick, the obtained polymer responded to a permanent magnet at room temperature in the air. From the ICP emission spectroscopic analysis, it was found that these polymers contained small amounts of transition metals, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Akkara et al ( 1991 ) reported on the polymerization of m -phenylenediamine with HRP/H 2 O 2 in an aqueous dioxane solution, and Kobayashi et al ( 1992 ) claimed that the enzymatic oxidation of o -PDA by HRP/H 2 O 2 in an aqueous dioxane leads to polymeric materials with an average molar mass of 20,000 g/mol, composed mainly of imino-2-aminophenylene units, while the simple nonenzymatic oxidation of o -PDA with H 2 O 2 yielded oligomeric products ( M w = 800) (Table 4 ). A comparative study of the HRP-catalyzed polymerizations of o -, m -, and p -PDA in homogeneous dioxane/water systems was performed by Ichinohe et al ( 1998a , b ). It was found that the polymeric yield significantly depends on the dioxane/water ratio, and the highest yields of polyphenylenediamines were obtained in a 15/85 (v/v) dioxane/water mixture (Ichinohe 1998b).…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 99%
See 2 more Smart Citations
“…Akkara et al ( 1991 ) reported on the polymerization of m -phenylenediamine with HRP/H 2 O 2 in an aqueous dioxane solution, and Kobayashi et al ( 1992 ) claimed that the enzymatic oxidation of o -PDA by HRP/H 2 O 2 in an aqueous dioxane leads to polymeric materials with an average molar mass of 20,000 g/mol, composed mainly of imino-2-aminophenylene units, while the simple nonenzymatic oxidation of o -PDA with H 2 O 2 yielded oligomeric products ( M w = 800) (Table 4 ). A comparative study of the HRP-catalyzed polymerizations of o -, m -, and p -PDA in homogeneous dioxane/water systems was performed by Ichinohe et al ( 1998a , b ). It was found that the polymeric yield significantly depends on the dioxane/water ratio, and the highest yields of polyphenylenediamines were obtained in a 15/85 (v/v) dioxane/water mixture (Ichinohe 1998b).…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 99%
“…It was found that the polymeric yield significantly depends on the dioxane/water ratio, and the highest yields of polyphenylenediamines were obtained in a 15/85 (v/v) dioxane/water mixture (Ichinohe 1998b). All phenylenediamines were also successfully polymerized by HRP/H 2 O 2 in a reversed micellar system of isooctane/water/AOT (Ichinohe et al 1997 , 1998a , c ). Polyphenylenediamines synthesized by both enzymatic methods, in a homogeneous dioxane/water system as well as in a heterogeneous reversed micellar isooctane/water/AOT system, showed ferromagnetic behavior (Ichinohe et al 1997 , 1998a ).…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen from Figure 1 that the saturation magnetization (M s ) and the coercive force (H c ) of the PANI-Ni are 4.5 emu g -1 (electromagnetic unit per gram) and about 55 Oe, respectively. The low coercive value implies that the PANI-Ni is a soft ferromagnetic material [14]. It is difficult to understand that the content of nickel in the resulting PANI is hardly related with the con- Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to tell whether PANi-TCNQ is a polymer with both conducting and ferromagnetic properties because no conductivity data are available in the literature [13]. Ichinohe and co-workers reported that ferromagnetic poly(m-phenylenediamine) was synthesized by using H 2 O 2 as an oxidant and horseradish peroxidase (HRP) as a catalyst in the mixture of aqueous buffer solution and 1,4-dioxane or in reversed micellar solution, and the obtained polymer was attracted to a permanent magnet, but no conductivity data were available in the paper, either [14]. Niu and co-workers reported the oxidation of m-phenylenediamine by using H 2 O 2 as an oxidant and horseradish peroxidase as a catalyst in 0.02 mol dm -3 B-R buffer solution, and 2,7-diaminophenazine was only obtained under the selected reaction condition [15].…”
Section: Introductionmentioning
confidence: 99%